2018
DOI: 10.1007/s12035-018-1234-2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant FGF21 Protects Against Blood-Brain Barrier Leakage Through Nrf2 Upregulation in Type 2 Diabetes Mice

Abstract: Blood-brain barrier (BBB) damage is a characteristic feature of diabetes mellitus pathology and plays significant roles in diabetes-associated neurological disorders. However, effective treatments for diabetes targeting BBB damage are yet to be developed. Fibroblast growth factor 21 (FGF21) is a potent regulator of lipid and glucose metabolism. In this study, we tested the hypothesis that recombinant FGF21 (rFGF21) administration may reduce type 2 diabetes (T2D)-induced BBB disruption via NF-E2-related factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…Upon stimulation with external stimuli, Nrf2 dissociates from the complex, translocate to the nucleus, binds to the antioxidant response element, and subsequently activates transcription aimed at cytoprotective and antioxidant factors, including HO‐1 (Loboda et al, ). Indeed, Nrf2 activation has been demonstrated to contribute to the upregulation of TJs expression and protection of BBB integrity (Yu et al, ). In addition, saponins in P. notoginseng are reported to motivate endogenous cytoprotective mechanism against oxidative injury in an Nrf2‐dependent manner (Huang et al, ; Zhou, Tang, Keep, Ma, & Xiang, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon stimulation with external stimuli, Nrf2 dissociates from the complex, translocate to the nucleus, binds to the antioxidant response element, and subsequently activates transcription aimed at cytoprotective and antioxidant factors, including HO‐1 (Loboda et al, ). Indeed, Nrf2 activation has been demonstrated to contribute to the upregulation of TJs expression and protection of BBB integrity (Yu et al, ). In addition, saponins in P. notoginseng are reported to motivate endogenous cytoprotective mechanism against oxidative injury in an Nrf2‐dependent manner (Huang et al, ; Zhou, Tang, Keep, Ma, & Xiang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, in unstimulated cells, Nrf2 is normally present in the cytoplasm, along (Loboda et al, 2016). Indeed, Nrf2 activation has been demonstrated to contribute to the upregulation of TJs expression and protection of BBB integrity (Yu et al, 2019). In addition, saponins in P. notoginseng are reported to motivate endogenous cytoprotective mechanism against oxidative injury in an Nrf2-dependent manner (Huang et al, 2014;Zhou, Tang, Keep, Ma, & Xiang, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we tested our hypothesis that poststroke administration of rFGF21 is protective against early BBB damage in T2DM mice via FGFR1-mediated elevation of cerebrovascular PPARγ activity. Two sets of experiments were designed as followed: in vivo study was performed using a focal stroke model in T2DM mice, treated with or without rFGF21 as we previously described [10], and an in vitro study was conducted using cultured human brain microvascular endothelial cells (HBMECs), insulted by a well-established hyperglycemia plus interleukin (IL)-1β exposure model to mimic in vivo situation of diabetic stroke as we previously described [15].…”
Section: Introductionmentioning
confidence: 99%
“…FGF21, a member of the FGF family, has been reported to regulate glycolipid metabolism, maintain energy balance, exert anti-inflammatory and antioxidation effects (36), protect the blood-brain barrier from traumatic brain injury, protect against blood-brain barrier leakage in T2DM (37,38), and facilitate remyelination of injured peripheral nerves and functional recovery. However, to the best of our knowledge, no research has shown that FGF21 can repair skin wounds.…”
Section: Discussionmentioning
confidence: 99%